A prospective and observational study to assess the efficacy of pregabalin versus Gabapentin in relieving early post operative neuropathic pain with respect to clinical and functional outcomes in patients undergoing open lumbar discectomy surgery - Garg, Rohit N.; Vaje, Shweta; Patil, Hrishikesh; Bajaj, Sanket (International Journal of Research in Orthopaedics, 2023)
Background: Post-operative neuropathic pain is one of the most dreadful complications following lumbar spine surgeries. Owing to the similarities in the pathophysiological and biochemical mechanisms underlying epilepsy and neuropathic pain, many anti-epileptic drugs (AEDs) like pregabalin and gabapentin are being used in the treatment of post-operative neuropathic pain. Methods: This prospective and observational study included a total of 60 patients out of 261 patients undergoing lumbar discectomy surgery, who postoperatively had neuropathic pain as diagnosed with LANSS score; and were randomly divided into pregabalin (n=30) and gabapentin (n=30) supplementation groups, and the efficacy was compared with respect to visual analog scale (VAS) score (clinically) and Oswestry disability index (ODI) score (functionally) at pre-operative and post-operative follow-ups; and also, total analgesia consumed. Results: No statistical differences were observed between any of the demographic variables and surgical levels operated upon between the two groups. Both the groups showed significant improvements in clinical (VAS) and functional (ODI) outcome as compared to pre-operative status. Leeds assessment of neuropathic symptoms and signs scale (LANSS) score was significantly increased in both the groups postoperatively till the 3rdmonthfollow-up, after which there was a significant decrease in the score. The Pregabalin group showed significant (p<0.05) improvement in VAS and ODI scores at the post operative 1st, 3rd, and 6th month, as compared to the gabapentin group; however, at other follow-ups the difference was insignificant. Total analgesia consumed was significantly higher in the gabapentin group. Conclusions: Our study concluded that both pregabalin and gabapentin are highly effective in the treatment of early post-operative neuropathic pain; showing encouraging clinical and functional improvements. Pregabalin had significantly better outcomes on short-term follow-ups; however, on longer follow-ups, both had similar beneficial outcomes. Pregabalin supplementation showed a significant analgesia-sparing effect as compared to gabapentin.